Sapiens : A Brief History of Humankind - Yuval Noah Harari (Harper Perennial, 2015)
Human cultures began to take shape about 70,000 years ago. There have been three major revolutions in human history: the cognitive revolution, the agricultural revolution, and the scientific revolution. Prehistoric humans (2 million years old or so) were no more important and impressive than other mammals. Homo Sapiens means â€œwise man.â€ Humans first evolved in Africa about 2.5 million years ago. The author believes it is unlikely Homo sapiens will survive for another 1,000 years.